How could you do thatn! [soundrecording] the abdication of character courage, conscience - Schlessinger, Laura; Harris, Rick.; Runette, John. (New York Harper Collins Publishers, 1996)
An argument for an ethical approach to life and an inspiration to rebuilding conscience, character and courage proving that doing good leads to feeling great. Demonstrates that personal values are our own responsibility.
An abridgement of the author's book, "How could you do thatn! the abdication of character, courage, conscience."
Read by the author, Dr. Laura Schlessinger.
Keywords: Courage; Character; Conscience; Ethics; Values; Psychology; Philosophy